Triaxial Compressive Failure Characteristics and Constitutive Model Study of Jurassic-Cretaceous Weakly Cemented Sandstone - Jinlong Cai; Wei Zou (Advances in Civil Engineering)
A conventional triaxial compression test of Jurassic-Cretaceous typical weakly consolidated sandstone from a mining area in Ordos, China, was conducted using an MTS816 tester. Results showed that, before the peak, the rock had a distinct yield stage. When the specimen reached its peak strength, the strength decreased rapidly and showed an obvious brittle failure. When the confining pressure was increased to 15 MPa, the decrease of strength was slow and the rock tended toward ductile failure. With the increase of confining pressure, the cyclic strain initially increased slightly, whereas the volumetric strain increased greatly and the rock sample was in a compression state. When the load reached a critical value, the curve was reversely bent, resulting in volume expansion, whereas the peak strength, residual strength, and elastic modulus increased with confining pressure, and Poisson’s ratio decreased with the confining pressure. In the model based on macroscopic failure rock, the expression of the relationship between fracture angle and confining pressure provided a solid theoretical basis for the direction and failure mode of the macroscopic crack. Based on the rock strength theory and Weibull random distribution assumption of rock element strength, the damage variable correction coefficient was introduced when the residual strength was considered. Then, the mathematical expression of the 3D damage statistical constitutive model was established. Finally, the theoretical curve of the established constitutive model was compared with the triaxial test curve, which showed a high degree of coincidence.